Marx y Freud en América Latina : política, psicoanálisis y religión en tiempos de terror - Bosteels, Bruno; Pinet, Simone; Bosteels, Bruno (Tres Cantos, Madrid, España : Akal, 2016)
This book assesses the untimely relevance of Marx and Freud for Latin America, thinkers alien to the region who became an inspiration to its beleaguered activists, intellectuals, writers and artists during times of political and cultural oppression. Bruno Bosteels presents ten case studies arguing that art and literature -- the novel, poetry, theatre, film -- more than any militant tract or theoretical essay, can give us a glimpse into Marxism and psychoanalysis, not so much as sciences of history or of the unconscious, respectively, but rather as two intricately related modes of understanding the formation of subjectivity.
Martí y Marx -- Marxismo y melodrama -- Sobre el sujeto de la dialéctica -- ¿Puede hablar el hombre nuevo -- Política, psicoanálisis, y religión en tiempos de terror -- La izquierda melancólica -- En el sombra de Mao -- Entre Freud y una mujer desnuda -- El detective posleninista -- Del Complot al Potlatch.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed August 10, 2019)
Keywords: Marx, Karl, -- 1818-1883 -- Influence; Freud, Sigmund, -- 1856-1939 -- Influence; Latin American literature -- History and criticism -- Theory, etc; Socialism and culture -- Latin America; Psychoanalysis and culture -- Latin America; Psychology and literature; Electronic books